Controls of Aurelia coerulea and Nemopilema nomurai (Cnidaria: Scyphozoa) blooms in the coastal sea of China: Strategies and measures - Feng, Song; Sun, Song; Li, Chaolun; Zhang, Fang (Frontiers in Marine Science, 2022)
Outbreaks of scyphozoan Aurelia coerulea and Nemopilema nomurai in the coastal sea of China are managed in recent years because they have severely jeopardized local socioeconomic development and ecological health. In this study, we propose specific strategies to control these blooms based on the different physio-ecological characteristics of their polyps, which can produce medusae by strobilation. High densities of A. coerulea polyps can survive chronically on the surfaces of some artificial constructions submerged in harbors or bays, China. Through buddings, they can resist the invasion of biofouling organisms and proliferate on the surfaces of some fouling organisms (e.g., ascidians, and bryozoans). However, N. nomurai polyps have not been recorded in natural environment. The in situ experiments found that polyps on settling plates fail to survive via podocysts due to severe biofouling invasion and post-strobilated degeneration in late spring and summer. As a result, the population size following is strongly dependent on the sexual recruitment of medusae during late summer and autumn. Therefore, we suggest that the reasonable governance strategy is to manage polyp populations together with biofouling organisms for A. coerulea blooms, however, with a focus on the medusa stage (particularly young medusae) to decrease the sexual reproduction in N. nomurai blooms. Accordingly, massive occurrences of A. coerulea in Qingdao Middle Port, China were alleviated by eliminating polyps and biofouling organisms on the undersurfaces of floating docks and then brushing the surfaces with modified alloprene paints. Some applicable control measures, including resource utilization of N. nomurai medusae and more severe and earlier summer fishing moratoriums, were used to possibly help restrain outbreaks of N. nomurai in Chinese coastal waters.